Myocardial fibrosis on cardiac magnetic resonance and cardiac outcomes in hypertrophic cardiomyopathy: a meta-analysis. Issue 17 (9th June 2015) - Briasoulis, Alexandros; Mallikethi-Reddy, Sagar; Palla, Mohan; Alesh, Issa; Afonso, Luis
Abstract : Objective: Late gadolinium enhancement (LGE) on cardiac MRI that indicates the extent of myocardial fibrosis in hypertrophic cardiomyopathy (HCM) is a potential risk factor of sudden cardiac death (SCD) in non-high-risk patients according to conventional clinical markers. Methods: The present study was designed to systematically review prospective trials and assess the association between LGE and SCD in HCM. We systematically searched the electronic databases, MEDLINE, PubMed, Embase and Cochrane for prospective cohort studies of the effects of LGE on clinical outcomes (SCD/aborted SCD, all-cause mortality, cardiac and heart failure death) in HCM. Results: We identified six clinical studies, examining 1414 patients without LGE and 1653 with LGE and an average follow-up of 3.05 years. The incidence of SCD/aborted SCD in patients with HCM and LGE was significantly increased as compared with patients without LGE (OR 2.52, 95% CI 1.44 to 4.4, p=0.001). The all-cause mortality and cardiac death rates were also significantly increased in patients with LGE. The extent of LGE was not significantly related to the risk of SCD. Conclusions: LGE is significantly associated with SCD risk, cardiac mortality and all-cause mortality in patients with non-high-risk HCM according to conventional risk factors.